Analysis of Public Service Performance of Government Apparatus at the Maridan Village Office in Sepaku District, Penajam Paser Utara Regency - Samad, Mohammad Azwar; Hamid, Muliyadi; Samad, Abdul (Newinera Publisher, 2024)
This study aims to analyze the performance of public services at the Lurah Maridan Office in Sepaku District, Penajam Paser Utara Regency. The primary focus of this research is to describe the extent to which the principles of effective and efficient public service are applied, as well as the measures taken by the local government to improve the quality of service provided to the community. The study uses a qualitative approach, with data collected through in-depth interviews with local government officials and members of the community to gather information on the practices and public perceptions regarding the services provided. The findings of the study indicate that the Lurah Maridan Office has made efforts to improve public service performance by implementing various strategic measures, such as utilizing technology to simplify administration, enhancing employee discipline, and conducting regular performance evaluations. However, challenges related to a shortage of human resources and limited infrastructure remain obstacles in achieving service efficiency and effectiveness. Overall, despite some challenges, the community reported improvements in the quality of services provided, with an increasing level of satisfaction.